Learning and Judgment Can Be Affected by Predisposed Fearfulness in Laying Hens - de Haas, Elske N.; Lee, Caroline; Rodenburg, T. Bas (Frontiers in Veterinary Science, 2017)
High fearfulness could disrupt learning and likely affects judgement in animals, especially when high fearfulness is part of an animals’ personality i.e. as trait anxiety. Here, we tested whether in laying hen chickens high fearfulness affects discrimination learning and judgement bias. Based on response to an open field at five weeks of age, birds were characterized as fearful (FC) by showing no walking or vocalizing, or as non-fearful (NFC) by showing walking and vocalizing. At adult age, birds (n=24) were trained in a go-go task to discriminate two cues (white or black) with a small or large reward. Birds that reached training criterion were exposed to three unrewarded ambiguous cues (25%, 50% and 75% black) to assess judgement bias. Task-acquisition took longer for FC birds than for NFC birds, due to left side-bias and more sessions needed to unlearn this side-bias. Changes in trial setup increased response latencies for FC birds but not for NFC birds. A larger number of FC birds than NFC birds chose optimistically in the last ambiguous trial (25% black). FC birds had a longer latency to choose in the ambiguous trial 75% black compared to NFC birds. Prior choice in ambiguous trials and preceding large or small trial affected latencies and choices for both types of birds. Our study showed that fearfulness was associated with differences in discrimination learning ability and judgement bias learning. It appeared that FC birds used a rigid response strategy during early learning phases by choosing a specific side repeatedly irrespective of success. FC birds were more affected by changes in the setup of the trials in comparison to NFC birds. We speculate that FC birds are more sensitive to changes in environmental cues and reward expectancy. These factors could explain how high fearfulness affects learning.